Crisis Response in Social Protection - Marzo, Federica; Mori, Hideki (World Bank, Washington, DC, 2013)
The main goal of this paper is to draw lessons from the past to better understand the role and potential of social protection in response to crisis, and support the definition of the World Bank social protection and labor strategy 2012-2022. This paper uses selected crises (1990-present), their social impact, and government responses to evaluate the social protection instruments deployed and provide lessons learned and possible directions for the future, including questions for further analytical work. While experience seems to suggest that governments and the World Bank are increasingly committed to the mainstreaming of social protection in crises prevention and management, important challenges and questions to be answered still remain to effectively protect populations, especially in the case of low Income countries and fragile states. Among the main messages emerging from the paper are, first, that crises are very diverse in origins, channels of transmission and impacts; second, preparing for crises by fiscal prudence and by setting programs in place is crucial to dispose of the necessary financial resources and to increase the speed and reach of the response; third, the design of permanent programs can be different from what is required for crisis management measures, especially in the aftermath of natural disasters. A solution could be to equip programs with ready-to-implement, standardized emergency toolkits.